Public Expenditure Management - Premchand, A. (International Monetary Fund, 1994)
This book, by A. Premchand, Assistant Director, IMF's Fiscal Affairs Department, provides a comprehensive discussion of the expenditure process in public authorities from a management perspective. It covers the various aspects, ranging from budget formulation to the courteous delivery of services to the public. In each, it considers the critical issues faced in industrial and developing countries and former centrally planned economies and discusses the efforts necessary to assure the public about the adequacy of public expenditure management machinery.